2016
DOI: 10.1186/s12955-016-0448-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Sinhalese version of MacNew Heart Disease Health Related Quality of Life Questionnaire in patients with stable angina

Abstract: BackgroundA Sinhalese version of a validated, disease-specific patient-reported heart disease health related quality of life instrument is lacking. The purpose of this study was to validate the interviewer-administered Sinhalese version of the MacNew Heart Disease Health-related Quality of Life Questionnaire (MacNew) in patients with clinically diagnosed stable angina.MethodsThe Sinhalese translation of the MacNew was carried using standard forward- backward translation technique. In this validation study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 21 publications
5
13
0
1
Order By: Relevance
“…The minimal important difference (MID) on the global MacNew and the three subscales is determined by 0.50 points as a significant change 25. The reliability of the total MacNew has been well established in a plethora of previous studies, with Cronbach's alpha coefficients ranging from 0.85 to 0.94 [27][28][29]. The Cronbach's alpha coefficient of the Korean MacNew in the current study was also high at 0.90 for the total scale, and 0.86, 0.85 and 0.88 for the emotional, physical and social subscales, respectively.…”
supporting
confidence: 60%
“…The minimal important difference (MID) on the global MacNew and the three subscales is determined by 0.50 points as a significant change 25. The reliability of the total MacNew has been well established in a plethora of previous studies, with Cronbach's alpha coefficients ranging from 0.85 to 0.94 [27][28][29]. The Cronbach's alpha coefficient of the Korean MacNew in the current study was also high at 0.90 for the total scale, and 0.86, 0.85 and 0.88 for the emotional, physical and social subscales, respectively.…”
supporting
confidence: 60%
“…All 14 items from the emotional dimension of the original MacNew were included in the emotional dimension of the Korean version, along with one additional item (Item 11, more dependent). Item 11 was loaded onto the social dimension in the original version and the physical dimension in the Sri Lankan version [12], and was not loaded onto any of the three dimensions in the Chinese [6] and Turkish versions [27]. The factor loadings of Item 11 across studies may be attributable to the cultural differences that occur when interpreting the statements of the instrument.…”
Section: Discussionmentioning
confidence: 99%
“…The original tool has 12 items that are crossloaded onto two or more factors [13]. Furthermore, although it varies across studies, previous studies reported that at least three items are cross-loaded onto two or more factors [6,7,12,26]. The K-MacNew also features seven items that are cross-loaded onto two factors, and one item is cross-loaded onto three factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations